2004
DOI: 10.1159/000075030
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Vascular Endothelial Growth Factor in Keloids: Relevance to Tissue Fibrosis

Abstract: Excessive scar or keloid shares common features of a benign dermal growth. Yet, in contrast to malignant tumor, a keloid does not expand beyond the dermis. What triggers the continuing growth of a benign lesion? Deficient or overabundant levels of vascular endothelial growth factor have been reported to contribute to impaired or excessive wound healing. Although numerous studies have examined the pathophysiology of impaired wounds, little information has been provided on mechanisms of exuberant healing. The mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
58
1
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 52 publications
5
58
1
3
Order By: Relevance
“…These results support the hypothesis that an altered balance of activator and inhibitor activities in the plasminogen system, in particular, an overexpression of PAI-1, may partly contribute to keloid formation and tissue fibrosis (40). Moreover, numerous studies revealed an abundant accumulation of growth factors and cytokines in keloids (1,31,32,63,64), some of which can be upregulated by hypoxia (50). These factors, such as insulin and insulin-like growth factors (IGFs) (5,12), fibroblast growth factor (FGF) (25), plateletderived growth factor (PDGF) (47), transforming growth factor (TGF), and tumor necrosis factor-␣ (TNF-␣) (49), in combination with local tissue hypoxia (16,17,27,66), may play an essential role in the regulation of PAI-1 expression.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…These results support the hypothesis that an altered balance of activator and inhibitor activities in the plasminogen system, in particular, an overexpression of PAI-1, may partly contribute to keloid formation and tissue fibrosis (40). Moreover, numerous studies revealed an abundant accumulation of growth factors and cytokines in keloids (1,31,32,63,64), some of which can be upregulated by hypoxia (50). These factors, such as insulin and insulin-like growth factors (IGFs) (5,12), fibroblast growth factor (FGF) (25), plateletderived growth factor (PDGF) (47), transforming growth factor (TGF), and tumor necrosis factor-␣ (TNF-␣) (49), in combination with local tissue hypoxia (16,17,27,66), may play an essential role in the regulation of PAI-1 expression.…”
supporting
confidence: 77%
“…Previous studies described an abundance of growth factors and cytokines (31,32,63,64) in the keloid milieu. During the inflammatory stage of wound healing, macrophages and neutrophils are activated and proinflammatory cytokines are released; among these is VEGF.…”
Section: Discussionmentioning
confidence: 99%
“…They are thick scar tissue of human skin, which have escaped the boundaries of the original wound to invade the surrounding normal skin. However, they are limited to the dermis unlike a malignant tumour [3]. Keloids were first described centuries ago in the Smith Papyrus, later in 1770 by Retz and in 1806 by Alibert, who proposed the current name [4].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the degree of keloid scar tissue bears little or no resemblance to the initial underlying injury, with trivial trauma resulting in severe, abnormal scar tissue (7). Although keloids have been previously reported to occur spontaneously (1,7,56,57), it is likely that these lesions had been caused by trivial or over-looked injury, such as insect bites or razor cuts (7,52). As such, the early classification of keloids into two groups; namely "true" keloids (spontaneous lesions devoid of previous trauma) and "false" keloids (arising from an initial trauma) has been entirely rejected (7).…”
Section: Human Leukocyte Antigen and Keloidsmentioning
confidence: 99%